Research on Cost Stickiness in International Journals: A Bibliometric Study - Komang Ayu Krisnadewi; Ballav Niroula; Sanju Kumar Singh (AKRUAL: JURNAL AKUNTANSI, 2022)
Contemporary points of view have posited that cost behavior is asymmetrical and tends to be sticky. The purpose of this study is to determine the development of cost behavior research, especially about cost stickiness, in reputable international journals. There are 142 articles that meet the criteria which have been obtained from the Scopus database. Bibliometric analysis has been performed with the help of the VOSviewer application. The results of the analysis show that research related to cost stickiness has increased in the last decade. The cost stickiness research consists of the following clusters: 1) the health industry; 2) labor costs; 3) social, environmental and sustainability issues; 4) corporate governance; 5) specific problems in manufacturing; and 6) leadership characteristics. The topics of research on cost stickiness that are still being researched are related to the role of the environmental community, business strategy, and the role of managerial leadership. In this analysis, the authors also show that articles that treat cost stickiness as an independent variable are limited. Based on the results of this analysis, we provide suggestions regarding opportunities for research on cost stickiness in the future.